Inequalities in referrals to social prescribing from primary care in England: A retrospective observational study - Efundem Agboraw; Anna Wilding; Luke Munford; Matt Sutton; Paul Wilson (PLoS ONE, 2026)
Background Social prescribing is a growing community health intervention and has been associated with improved patient outcomes. However, the evidence around inequalities in referrals shows varying patterns. We aim to examine referrals to social prescribing link workers funded by the Additional Roles Reimbursement Scheme in England. Methods We conducted a retrospective observational population-based study, using primary care data from Clinical Practice Research Datalink (CPRD) Aurum from 1st July 2019–31st March 2024. Participants included over 12 million patients aged 16 years or older. We examined the likelihood of offers and subsequent referrals to social prescribing by patient- and area-level characteristics using logistic regression and report odds ratios (ORs). Results Since July 2019, approximately 4% of the CPRD population have been offered a referral to social prescribing. 77·7% of those were referred. Patients who are: female, older, living in less deprived areas and have multiple long-term conditions have higher odds of being offered social prescribing (Female OR = 1·35, 95% CI [1·32 to 1·38] p < 0.001). Factors such as region, rurality, and ethnicity do not result in inequalities in offers compared to the general population. Of those offered, we find that those who are female, those from non-white ethnicities (Black, Asian and Mixed), and have multiple long-term conditions had higher odds of accepting offers of referrals (being referred). Conclusion Referrals to social prescribing have increased following the national rollout of link workers. However, inequalities in offers and referrals to social prescribing have been identified by patient and area-level factors. Our findings indicate that policies should improve awareness of social prescribing in deprived areas and direct certain patient groups, such as ethnic minorities, males and those older to the benefits of being referred to social prescribing.